2014
DOI: 10.1108/cms-07-2013-0125
|View full text |Cite
|
Sign up to set email alerts
|

Institutional influence, cognition and competence of top managers and innovative firms

Abstract: Purpose – This paper aims to explore the relationship between the role of entrepreneurs and the innovation investment propensity of Chinese firms. This study is expected to enhance our understanding about the competence building of top management team for innovative development. Design/methodology/approach – The analytical framework draws upon the recent theoretical progress about innovative firms, cognition and competence building of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Future studies may implement other contexts to provide a clear picture of the relationship between these constructs. Finally, Feng et al (2014) argued that Chinese firms should proactively reconfigure their activities to transform from a manufacturing-based economy to an innovative economy. These authors also indicated that enhance our understanding about the competence building of top management team for innovative development is very important.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may implement other contexts to provide a clear picture of the relationship between these constructs. Finally, Feng et al (2014) argued that Chinese firms should proactively reconfigure their activities to transform from a manufacturing-based economy to an innovative economy. These authors also indicated that enhance our understanding about the competence building of top management team for innovative development is very important.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, firms' ability to integrate new ideas and knowledge with the firms' existing capabilities is subject to managers' ability to utilise scanning activities to develop cognitive schemas about the environment and to identify new trends and opportunities. These cognitive schemas can affect how managers conceptualise their businesses and make critical decisions for resource allocation (Feng et al, 2014), which supports the firms' ability to achieve external and evolutionary fit (Kor and Mesko, 2013). This may explain why managers develop different representations as a response to the same environmental change.…”
Section: The Complementary Role Of Cognition Of Environment and Cognition Of Resourcesmentioning
confidence: 96%
“…Cognition of resources refers to a firm's responses to environmental changes that are shaped by developing cognitive schemas that reflect the manager's understanding of the potential uses of a firm's resources. Cognition of resources relates to the firm's ability to use the resources for alternate services (Autio et al, 2011, Danneels, 2011, Martin and Bachrach, 2018; and to achieve competitive strategies (Combe et al, 2012, Eggers and Kaplan, 2013, Feng et al, 2014. It has also been considered as an understanding of resource fungibility (Danneels, 2011), generic (high) vs. specific (low) fungibility.…”
Section: Cognition Of Resourcesmentioning
confidence: 99%
“…NREC was founded by and has been led by an academician of the National Academy of Engineering. Its eight senior management team members, including executives responsible for operations and finance, have all worked in the enterprise for nearly 20 years and have technical and product development experience (Feng et al , 2014). As a result, its decision-makers have a strong understanding of engineering information and issues.…”
Section: Case Study: the Growth And Internalization Of Nr Electricmentioning
confidence: 99%